The Role of Mass Media in The Emergence of Deviant Behavior in Society - Sinaga, Lianda Rachmadany; Larasati, Ayu (Jurnal Indonesia Sosial Sains, 2024)
One of the primary studies in the sociology of communication is the influence of mass communication in society. Media is a communication transmitter or "channel" that includes newspapers, magazines, radio, television, movies, posters, and banners. The medium can be used and received by the communicator, but the medium can affect more than one communicator. This can affect many communicants regardless of the number of communicators; this means if a communicator uses any of the mentioned mediums, they can easily influence the behaviour of society as a whole. Behaviour change can have positive and negative impacts, which is why learning or understanding the role of mass media in communication is very important. There are many cases where the use of mass media can lead to deviant actions. Deviant actions that appear more often today will involve the mass media, meaning that the mass media has a significant influence. The impact of mass media can be seen in our daily lives, and mass media has become a basic need of human society as a whole. With mass media incorporated into everyday life, any information can be gathered. Such information can be the difference between a positive impact and a negative impact, it all depends on the user (communicator). This journal will focus on how mass media can trigger deviant societal actions and how to overcome them.